2019
DOI: 10.1016/j.ebiom.2019.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial FAM3A positively regulates post-ischaemic angiogenesis

Abstract: Background Angiogenesis improves reperfusion to the ischaemic tissue after vascular obstruction. The underlying molecular mechanisms of post-ischaemic angiogenesis are not clear. FAM3A belongs to the family with sequence similarity 3 (FAM3) genes, but its biological function in endothelial cells in regards to vascular diseases is not well understood. Methods Gain- and loss-of-function methods by adenovirus or associated-adenovirus (AAV) in different models were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Returning to the new publication by Xu et al, the localization of FAM3A in endothelial cells was first confirmed as being mitochondrial by immunostaining and subcellular fractionation [3]. Despite the fact that endothelial cells are usually primarily glycolytic, they contain mitochondria which have important functions in various aspects of cell physiology, from the regulation of Ca 2+ signalling dynamics, to the control of cell death pathways such as apoptosis [8].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Returning to the new publication by Xu et al, the localization of FAM3A in endothelial cells was first confirmed as being mitochondrial by immunostaining and subcellular fractionation [3]. Despite the fact that endothelial cells are usually primarily glycolytic, they contain mitochondria which have important functions in various aspects of cell physiology, from the regulation of Ca 2+ signalling dynamics, to the control of cell death pathways such as apoptosis [8].…”
mentioning
confidence: 99%
“…Despite the fact that endothelial cells are usually primarily glycolytic, they contain mitochondria which have important functions in various aspects of cell physiology, from the regulation of Ca 2+ signalling dynamics, to the control of cell death pathways such as apoptosis [8]. When endothelial FAM3A expression was increased, this caused an increase in ATP production and secretion, which was then able to bind to and activate plasma membrane P2 receptors, causing an increase in cytosolic Ca 2+ levels [3]. This stimulated the transcription of VEGF-A, leading to an increase in endothelial angiogenesis [3].…”
mentioning
confidence: 99%
See 3 more Smart Citations